La petite mort: três sôfregos momentos no cinema - Peixe, Viviane Rodrigues (2015)
The research aims to the representation of orgasm in the cinematography of three European films Êxtase (1933); Último Tango a Parigi (1972) e La Vie D´Adèle – Chapitres I et II (2013) films in which the motor aesthetic experience is sex (and orgasm). It is well known that cinema lived, in its beginnings, a moment of great freedom, but, didn‘t take long for movie industries to impose censorship of all kinds. Both, sex and orgasm, are part of the imagery rhetoric of cinema can be an audiovisual diary of human questions, prospects, fantasies and experiences, as many authors argue. Through the films chosen the dissertation seeks to reflect about the body, eroticism, pornography and orgasm in society considering that, they are treated as a projection of the real, represented (in)faithfully on screen. In all movies: sex as a social experience of aesthetic importance. These films also are historically important for cinematic art. To form such an intention was chosen weave reports on the body, orgasm and desire. In the plot was important interlacing and also scale the differences of film approaches about eroticism and pornography. Also was chosen traverse about the limitations socially imposed to the film manifestations of nudity - and afterwards, sexual intercourse - were systematized and regulated through a series of maneuvers of censorship codes, reports and other strategies of various reactionary groups. It was important also illustrate that the transgression was present in every moment of tightening censorship in an attempt to free the creative power in the construction of actions of those (and other) film narratives here, also, illustrated. Therefore, the direction of photography –and the work done by it - was chosen to articulate issues of filmic order that the analysis made from reading images and sounds of the three scenes in question - taking into consideration aesthetic and technical issues – illustrate, finally, differences and similarities between their contexts and approaches. All the proposed questions and their interrelationships seek to contextualize and conceptualize issues for the perception, at first, from contexts that lead to think about the pre-production and production of cinematographic photography of those works. Each, in turn, stated in its time, daring to a creative action that translate an intimate, but public, dimension, under a conservatism prism: the representation of orgasm. Recalling that this is also a story, not only from censorship, but mainly, from transgression.